Effect of Cold Exposures on Thyroid Activity and Low-Molecular Weight Polypeptides Spectrum in Rats - Shylo, A. V.; Ventskovskaya, E. A.; Semenchenko, A. Yu.; Babiychuk, G. A. (Problems of Cryobiology and Cryomedicine, 2024)
The resistance to cold in mammals is known as forming within several weeks of continuous exposure to cold. The intermittent cold exposures were shown as capable to result in an increased organism’s resistance to cold as well. The most pronounced and stable thermogenic effects under cold exposure are caused by such thyroid hormones as thyroxine (T4) and triiodothyronine (T3). The changes in the level of thyroid hormones and low-molecular weight polypeptides under continuous long-term cold exposure (LTCE) and rhythmic cold one (RCE) have been studied. The LTCE resulted in a dramatic long-term increase in T4 concentration compared to the control level. The T4 level was also statistically and significantly increased in rat blood serum with RCE of –12°C, whereas in animals with RCE of 10°C the only tendency to its augmentation is observed. The triiodothyronine level under the studied cold effects remained statistically and significantly unchanged. In addition, the certain concentration redistribution of low-molecular weight polypeptides (LMWP), having no pathological nature and being typical for the specific cold exposure, may be observed in blood plasma after LTCE and RCE. The very fact that an increase in adaptation capacities after RCE of –12°C results, as in LTCE case as well, at the background of thyroid system activation may testify to that as an essential factor to trigger the mechanisms involved into cold adaptation formation.